Cytotoxic Activity of Extracts from Plants of Central Argentina on Sensitive and Multidrug-Resistant Leukemia Cells: Isolation of an Active Principle from Gaillardia megapotamica - González, María Laura (2018)
Plants are a significant reservoir of cytotoxic agents, including compounds with the ability to interfere with multidrug resistant (MDR) cells. With the aim of finding promising candidates for chemotherapy, 91 native and naturalized plants collected from the central region of Argentina were screened for their cytotoxic effect toward sensitive and MDR P-glycoprotein (P-gp) over-expressing human leukemia cells by means of MTT assays. The ethanol extracts obtained from Aldama tucumanensis, Ambrosia elatior, Baccharis artemisioides, Baccharis coridifolia, Dimerostemma aspilioides, Gaillardia megapotamica and Vernonanthura nudiflora presented outstanding antiproliferative activity at 50 ug/mL, with inhibitory values from 93 to 100%, when tested on the acute lymphoblastic leukemia (ALL) cell line CCRF-CEM and the resistant derivative CEM-ADR5000, while 70-90% inhibition was observed against the chronic myelogenous leukemia (CML) cell K562 and its corresponding resistant subline, Lucena 1. Subsequent investigation showed these extracts to possess marked cytotoxicity with IC50 values ranging from 0.37 to 29.44 ug/mL, with most of them below 7 ug/mL, and with ALL cells, including the drug-resistant phenotype, being the most affected. G. megapotamica extract was found to be one of the most effective, and bioguided fractionation yielded helenalin (1). The sesquiterpene lactone displayed IC50 values of 0.63, 0.19, 0.74 and 0.16 ug/mL against K562, CCRF-CEM, Lucena 1 and CEM/ADR5000, respectively. These results support the potential of these extracts as a source of compounds for treating sensitive and multidrug-resistant leukemia cells, and support compound 1 as a lead for developing effective anticancer agents.